Management of Learning Facilities and Infrastructure to Enhance Educational Quality in Elementary Schools of Aceh Tamiang Regency - Saipin Ali Muhtaram; Munawar Munawar; Abdurrahman Abdurrahman (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study investigates the administration of educational facilities and infrastructure as a strategic initiative to enhance the quality of elementary education in Aceh Tamiang Regency. The research used a qualitative descriptive methodology centred on the fundamental managerial activities of planning, organizing, implementing, and evaluating, engaging principals, teachers, and facilities managers from SD Negeri Pusung Kapal, SD Negeri Tangsi Lama, and SD Negeri Tualang. Data were gathered by interviews, observation, and documentation, then analysed through data reduction, data display, and conclusion formulation. The findings indicate that the three institutions have implemented a methodical and cooperative framework for managing buildings and infrastructure. During the planning phase, the needs assessment relies on field data and is consistent with formal documents, including the School Work Plan (RKS) and the School Activity and Budget Plan (RKAS), thereby assuring stakeholder engagement. The organizing phase demonstrates a distinct allocation of roles and duties, bolstered by efficient interdepartmental collaboration. The implementation phase emphasizes that the procurement and exploitation of learning materials are conducted in accordance with instructional requirements, with active engagement from educators and facilities staff. During the evaluation phase, ongoing monitoring facilitates prompt maintenance and enhancement. The study emphasizes a participative, coordinated, adaptable, and context-sensitive management paradigm that fosters educational quality improvement, illustrating that collaborative resource management can enhance learning environments even in resource-constrained situations.